Effects of outdoor plant varieties on performance, egg quality, behavior, and economic analysis of Turkey local chicken from 20 to 36 weeks of age - Aygun, A; Narinc, D; Özköse, A; Arısoy, H; Acar, R; Uzal, S; Bulut, C (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was carried out to examine the effects of three plant combinations (white clover-perennial ryegrass, bird’s-foot trefoil-perennial ryegrass, and alfalfa-perennial ryegrass) planted in the outdoor area of ​​the free-range system on the performance, egg quality, and behavioral characteristics of Turkey local chicken. Performance characteristics of chickens (egg production, feed consumption, feed efficiency, broken egg rate, dirty egg rate, ground laying rate) were evaluated at 4-week intervals from 20 weeks to 36 weeks of age. In the study, the local layer genotype ATAK-S was used. Each group in the study consisted of 3 different plant varieties, formed from 4 replications. The mean values of hen-day egg production, and hen-day cumulative egg yield of layers in experimental groups were found to be between 91.16% and 94.76%, and between 87.89 and 91.67 %, respectively, and there was no statistical difference between the experimental groups. Similarly, there were no statistical differences between the experimental groups in terms of feed consumption, feed efficiency, egg weight, egg mass, broken-cracked egg ratio, or internal and external egg quality characteristics. There were no differences between the experimental groups in terms of time budgets allocated to various behavioral characteristics. In this study, outdoor area use was found to be quite high (41.04-41.56%) in all experimental groups. As a result, it was determined that the use of white clover-perennial ryegrass, bird’s-foot trefoil-perennial ryegrass, and alfalfa-perennial ryegrass vegetation combinations in the free-range system encourages layers to go to the outdoor. In addition, it has been found that these practices have positive effects on birds in terms of both their performance and their well-being.